2017
DOI: 10.1111/nph.14964
|View full text |Cite
|
Sign up to set email alerts
|

The NBLRR gene Pm60 confers powdery mildew resistance in wheat

Abstract: Powdery mildew is one of the most devastating diseases of wheat. To date, few powdery mildew resistance genes have been cloned from wheat due to the size and complexity of the wheat genome. Triticum urartu is the progenitor of the A genome of wheat and is an important source for powdery mildew resistance genes. Using molecular markers designed from scaffolds of the sequenced T. urartu accession and standard map-based cloning, a powdery mildew resistance locus was mapped to a 356-kb region, which contains two n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
161
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 180 publications
(182 citation statements)
references
References 49 publications
1
161
0
1
Order By: Relevance
“…In wheat, arrays of powdery mildew R genes ( Pm genes and temporarily designated genes) and alleles have been documented over 30 years, and in this review we have provided an updated list based on current knowledge (Table ). Of these powdery mildew resistance genes documented in the wheat gene pool, only six ( Pm2 , Pm3 , Pm8 , Pm17 , Pm21 , and Pm60 ) have been cloned to date, all encoding proteins of the NLR class (Yahiaoui et al , 2004; Cao et al , 2011; Hurni et al , 2013; Sanchez‐Martin et al , 2016; Xing et al , 2017; He et al , 2018; Singh et al , 2018; Zou et al , 2018). The gene‐for‐gene interaction always results in the host having a full resistance rating to the pathogen.…”
Section: Resistance Types For Powdery Mildewmentioning
confidence: 99%
“…In wheat, arrays of powdery mildew R genes ( Pm genes and temporarily designated genes) and alleles have been documented over 30 years, and in this review we have provided an updated list based on current knowledge (Table ). Of these powdery mildew resistance genes documented in the wheat gene pool, only six ( Pm2 , Pm3 , Pm8 , Pm17 , Pm21 , and Pm60 ) have been cloned to date, all encoding proteins of the NLR class (Yahiaoui et al , 2004; Cao et al , 2011; Hurni et al , 2013; Sanchez‐Martin et al , 2016; Xing et al , 2017; He et al , 2018; Singh et al , 2018; Zou et al , 2018). The gene‐for‐gene interaction always results in the host having a full resistance rating to the pathogen.…”
Section: Resistance Types For Powdery Mildewmentioning
confidence: 99%
“…However, some cloned genes of disease resistance in plants were reported to be not significantly up-regulated expression after pathogens inoculation. For example, Zou et al (2017) cloned wheat powdery mildew resistance gene Pm60 using standard map-based cloning, and showed that the transcript levels of Pm60 were no significantly difference after Bgt E09 infection at various time points by qRT-PCR [9]. In addition, Li et al (2017) discovered the expression level of broad-spectrum blast resistance gene bsr-d1 in rice was also not induced before and after blast infection [41].…”
Section: Discussionmentioning
confidence: 99%
“…Of which, 4,382 unigenes were differentially expressed genes (DEGs) in TA7733 post vs before Bgt -inoculation, and the remaining 2,896 unigenes had expression levels of no significant difference. In consideration of the fact that expression levels of some cloned resistance genes did show no significant difference before and after pathogen infection [9,41], we also take into account these 2,896 unigenes as putative candidate genes involved in powdery mildew resistance from chromosome 2M b .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations